The relationship between the emotional intelligence of managers and digital burnout among teachers in light of the digital transformation of education in Lebanon (The International Journal of Educational Sciences and Arts, 2026)
The study aimed to examine the relationship between a principal's emotional intelligence and teachers' digital burnout in the context of Lebanon's digital transformation of education. A mixed-methods approach was adopted—specifically, a sequential explanatory design. The quantitative component employed a descriptive-correlational method to describe the relationship between the two variables using a questionnaire, while the qualitative component utilized a descriptive-analytical method to analyze responses from interviews with principals. The study population consisted of a simple random sample of 231 intermediate-level teachers from selected schools, whereas the purpose of the interviews comprised five intermediate school principals.A questionnaire, designed specifically for the study, was distributed to the participants. The results revealed a relationship between the principal's emotional intelligence and teachers' digital burnout at significance levels of α=0.01 and α=0.05. A statistically significant inverse effect of emotional intelligence on digital burnout was observed, with a regression coefficient B = -0.398 (t = -5.697); this effect is supported by the 95% BCa confidence intervals, which range from -0.529 to —0.255 and do not include zero. Furthermore, the results indicated an inverse correlation between the principal's ability to regulate emotions and teachers' digital burnout, with a correlation coefficient of -0.151.The results revealed no statistically significant differences in teachers' digital burnout by gender, as the p-value was 0.817 (greater than 0.05). Similarly, regarding the experience variable, the significance value was 0.831 (greater than 0.05). However, regarding the skill level variable, the results showed statistically significant differences in teachers' digital burnout, with a significance value of 0.006 (less than 0.05).The study offered several recommendations, including organizing training programs and workshops for school principals focused on emotional intelligence skills; fostering a healthy school climate characterized by appreciation and psychological and professional support to mitigate digital burnout; providing technological support to teachers to alleviate digital-related pressures and enhance their digital competencies; and conducting periodic assessments of teachers' levels of digital burnout.
Keywords: Emotional Intelligence; Self-Awareness; Empathy; Digital Burnout; Technological Exhaustion; Digital Emotional Depletion